A new species of cephalaspidean sea slug of the genus Melanochlamys Cheeseman, 1881 (Heterobranchia: Aglajidae) from the Bay of Bengal, India. (2nd October 2022) - Tudu, Prasad Chandra; Sajan, Sheikh; Roy, Soumen; Mukhapadhyay, Amit; Tripathy, Basudev; Mohapatra, Anil
ABSTRACT: A new species of head-shield sea slug, Melanochlamys bengalensis, is described from the northern part of the eastern coast of India using both external and internal morphological characters. Its novel status is supported by a molecular analysis. The maximum likelihood (ML) genetic tree (COI gene sequence) indicates that the new species represents a distinct clade compared to the other species of the genus Melanochlamys . The K2P distance of the new species is 16.2–23.7%, which is considerably more than the other congeners. This species was collected from the intertidal zone of the sandy beaches of Bakkhali, Tajpur, New Digha, Udaipur, Talsari, Chandipur and Kanika Island. Additionally, the list of valid species and distribution of all members of the genus Melanochlamys is presented herein.